2010
DOI: 10.1208/s12249-010-9506-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Chemical Durability of Glass Used in the Pharmaceutical Industry

Abstract: Delamination, or the generation of glass flakes in vials used to contain parenteral drug products, continues to be a persistent problem in the pharmaceutical industry. To understand all of the factors that might contribute to delamination, a statistical design of experiments was implemented to describe this loss of chemical integrity for glass vials. Phase I of this study focused on the effects of thermal exposure (prior to product filling) on the surface chemistry of glass vials. Even though such temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 26 publications
1
57
1
1
Order By: Relevance
“…10,29) Considering the fact that sulfur treatment suppressed the particle formation, dealkalization might have an effect on the suppression of particle formation. In contrast, SiO 2 coating is also known to protect the surface from alkali elution, 2,12) however, no suppression effects of the SiO 2 coating on the particle formation were shown in this study.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…10,29) Considering the fact that sulfur treatment suppressed the particle formation, dealkalization might have an effect on the suppression of particle formation. In contrast, SiO 2 coating is also known to protect the surface from alkali elution, 2,12) however, no suppression effects of the SiO 2 coating on the particle formation were shown in this study.…”
Section: Resultscontrasting
confidence: 67%
“…At that time, we also measured the concentration of Si, which is known as indicator of delamination. 12) This extraction was conducted at a high temperature for short time (121± 1°C, 10 min) to keep the concentrations from any undesirable effects during extracting.…”
Section: The Correlation Of the Particle Formation And Al And Si Concmentioning
confidence: 99%
See 1 more Smart Citation
“…4,16) On the other hand, SiO 2 coating, a technique to coat the surface with silica, is known to be able to avoid delamination from the glass surface. 2,6) However, our previous study showed that sulfur-treated vials showed a protective effect against the Al-containing particles' formation, while otherwise the SiO 2 coating did not have any protective effects.…”
mentioning
confidence: 90%
“…Delamination, which is indicated by the presence of glass flakes, is the most well-known phenomenon and is the result of corrosive attack on the inner surface of the glass container. [4][5][6][7][8][9][10] United States Pharmacopeia (USP) ‹1660› describes factors of delamination on the surface of glass vials filled with drug solution, and also introduces tools for selecting an appropriate glass container from the point of view of avoiding delamination. 11) Among several literatures describing the propensity of forming delamination, Guadagnino has suggested that the silicon dioxide (SiO 2 ) concentration in an extract solution is an efficient indicator of glass dissolution.…”
mentioning
confidence: 99%